Effects of percussive massage therapy on fascia echo intensity and fascia thickness in firefighters with chronic non-specific low back pain: a randomized controlled trial - Chao Yang; Ying Li; Wiraphong Sucharit; Wichai Eungpinichpong; Xingyu Huang (BMC Complementary Medicine and Therapies)
Abstract Background Chronic non-specific low back pain (CNSLBP) is prevalent among firefighters and may negatively affect their job performance. Alterations in the thoracolumbar fascia (TLF) structure are associated with CNSLBP. Percussive massage therapy (PT) has demonstrated potential in modifying fascial properties and alleviating pain. However, its effects on TLF structure in CNSLBP patients have not been thoroughly investigated. This study evaluates the effects of 6 weeks of PT on TLF echo intensity, thickness, pain, and disability in firefighters with CNSLBP, utilizing ultrasound imaging as a primary assessment tool. Methods This six-week randomized controlled trial involved 38 firefighters with CNSLBP. Participants were randomly assigned 1:1 to either the PT group (receiving PT and core stability exercise) or the control group (receiving only core stability exercise). TLF echo intensity and thickness were measured using ultrasound imaging, and disability was assessed using the Roland-Morris Disability Questionnaire (RMQ) at baseline and post-intervention. Pain was measured using the Visual Analog Scale (VAS) at baseline, immediately after the first intervention, three weeks post-intervention, and post-intervention. Paired t-tests were conducted to analyze within-group changes in RMQ and ultrasound data, while ANCOVA was used to assess between-group differences, and repeated measures ANOVA for VAS scores. Results Participants in the PT and control groups were aged 26.6±4.1 and 23.6±1.7 years, respectively, with BMI of 23.1±1.8 and 21.8±1.2 kg/m². The PT group showed significant reductions in bilateral TLF echo intensity post-intervention (left side: mean difference -6.4, 95% CI -9.7 to -3.1, p < 0.001, effect size 0.67; right side: mean difference  -7.6, 95% CI -11.8 to -3.3, p < 0.01, effect size 0.60). Changes in TLF thickness were not statistically significant (p > 0.05). The PT group demonstrated significantly lower VAS scores than the control group (mean difference - 0.626, 95% CI -1.087 to -0.165, p = 0.009, effect size 0.63). RMQ scores decreased by -1.3 (95% CI -2.1 to -0.4, p < 0.01, effect size 0.5). Conclusion Six weeks of percussive massage therapy significantly reduced thoracolumbar fascia echo intensity, alleviated pain, and improved functional disability in firefighters with chronic non-specific low back pain, but was not effective in altering fascia thickness. Percussive massage therapy emerges as an effective and safe strategy for managing chronic non-specific low back pain in firefighters. Trial registration Retrospectively registered in Thai Clinical Trials Registry (TCTR20221223001) on December 22, 2022.